A proposed nosology of inborn errors of metabolism - Ferreira Lopez, Carlos R; Blau, Nenad (Genetics in medicine, 2019)
We propose a nosology for inborn errors of metabolism that builds on their recent redefinition. We established a strict definition of criteria to develop a self-consistent schema for inclusion of a disorder into the nosology. We identified 1015 well-characterized inborn errors of metabolism described in the literature. In addition, there are 111 less well-characterized conditions that may be inborn errors but do not meet strict criteria for inclusion in the current nosology. We provide a master list of all currently recognized inborn errors of metabolism grouped according to their pathophysiological basis, with the hope of setting a standard against which new errors should be defined, as well as to promote awareness and foster collaboration in the area. With the rapid advances in the field of genetics in recent years, it is likely that this nosology will need to be updated in the near future, a process that will benefit from broader input and collaboration of experts in the field to improve future versions of the proposed classification.
Published: 08 June 2018
Gesehen am 26.07.2019